Katekis Sebagai Animator Dalam Membangun Gereja Lokal - Alfridus Yorianto Sasi; Instansakti Pius X (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Catechists not only have the task of teaching and preparing people to understand and appreciate the teachings of the Catholic religion, but also play a role as the main mover in building a climate that welcomes and promotes active participation of people in the life of the Church. This article aims to explain the important role of catechists as animators in building the local Church. This research is a qualitative descriptive type with data collection techniques in the form of literature study. The research results show that the role of catechists as local Church animators is carried out by educating people about Catholic teachings and Church beliefs, building foundations of faith, helping people face challenges, promoting unity in the local Church, and increasing participation in Church life.